2017
DOI: 10.1038/ncomms14902
|View full text |Cite
|
Sign up to set email alerts
|

Real-time reliable determination of binding kinetics of DNA hybridization using a multi-channel graphene biosensor

Abstract: Reliable determination of binding kinetics and affinity of DNA hybridization and single-base mismatches plays an essential role in systems biology, personalized and precision medicine. The standard tools are optical-based sensors that are difficult to operate in low cost and to miniaturize for high-throughput measurement. Biosensors based on nanowire field-effect transistors have been developed, but reliable and cost-effective fabrication remains a challenge. Here, we demonstrate that a graphene single-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
351
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(374 citation statements)
references
References 61 publications
14
351
1
1
Order By: Relevance
“…The increased ssDNA capture probe capacity can extend the detection limit and also dynamic range. 23,24 In addition, the micropillar array increases the interaction between biomolecules and the substrate, as the surface area in contact with any given solution is significantly higher. To further increase the probe binding capacity, we can increase the aspect ratio of PDMS micropillars and the microchannel length.…”
Section: Discussionmentioning
confidence: 99%
“…The increased ssDNA capture probe capacity can extend the detection limit and also dynamic range. 23,24 In addition, the micropillar array increases the interaction between biomolecules and the substrate, as the surface area in contact with any given solution is significantly higher. To further increase the probe binding capacity, we can increase the aspect ratio of PDMS micropillars and the microchannel length.…”
Section: Discussionmentioning
confidence: 99%
“…The change of electric potential of graphene can be explained by the negative electrostatic gating effect. As DNA has a negatively charged triphosphate group, it can modulate the Fermi level of graphene by inducing excess hole carriers and in turn shift cnp to the positive direction [24,25]. Figure 4(a) shows the transfer characteristics of DNA probe-modified G-FETs before and after addition of target RNAs (full-complementary) with different concentration from 0.1 fM to 1 pM.…”
Section: Resultsmentioning
confidence: 99%
“…Nanomaterial such as carbon nanotubes and graphene nanosheets are usually added into chitosan as enhancement materials . It is reported that the graphene nanosheets can improve the uniformity and evenness of chitosan thin film and promote DNA hybridization reaction.…”
Section: Recent Developmentsmentioning
confidence: 99%